APPRAISAL SYSTEM RECOGNIZED IN THE JAKARTA POST'S EDITORIAL “THE ASEAN CAGE” ON JULY 20th, 2011 - Liliek Soepriatmadji; Dhion Meitreya Vidhiasi (Universitas Stikubank (UNISBANK) Semarang, 2012)
This study attempts to construe (1) the appraisal devices recognized in the “The Asean Cage” text? (2) how the readers may be positioned in the text. When a categorical technique based on Appraisal theory proposed by Martin and White (2005) was applied, the writers found out that the editorial text displays appraisal devices in different percentages (Affect-Attitude (3.03%), Judgment-Attitude (45.45%) and Appreciation-Attitude (51.52%); Mono-glossic-Engagement (0%), Dialogic Contraction-Engagement (58.3%) and Dialogic Expansion-Engagement (41.7%); Force-Graduation (97.8%) and Focus-Graduation (2.2%). Based on the analysis of Appraisal System, the readers may be positioned as those who accept the editor’s assessment about the condition between Indonesia and ASEAN. Key words: Editorial, Appraisal System, Attitude, Engagement, Graduation